Analisis Putusan Pengadilan Agama Kota Malang tentang Dispensasi Kawin - Caesar Abdullah Salam; Ach. Minanur Rohman; Affrido Galuh Mulyono; Ahmad Falahuddin Assegaf Antariksa; Kevin Azzura Mylinda Handono; Salsabil Yusril Kamal; M. Romdlon (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2020)
Abstract: This article discusses the decision of Malang City Religious Court No. 0306 / Pdt.P / 2020 / PA.Mlg regarding the dispensation of marriage. This research is library research and is qualitative in nature. The primary data source is decision No. 0306 / Pdt.P / 2020 / PA.Mlg regarding the dispensation of marriage, supported by secular data sources from books and journals. The data obtained were analyzed juridically. The results of the study concluded that decision no. 0306 / Pdt.P / 2020 / PA.Mlg regarding the dispensation of marriage, the judge granted the applicant's petition with the consideration that the prospective wife was 2 months pregnant, and was based on the rules of dar 'al-mafasid muqaddam ala jalb al-mashalih, for the sake of mutual benefit, especially for future wives and children to be conceived. Based on PERMA Number 5 of 2019 concerning Guidelines for adjudicating Applications for Dispensation of Marriage and Marriage Law Number 1 of 1974 concerning Marriage, the judge's decision did not violate the applicable rules. Based on this, it is hoped that the community, especially teenagers, to keep themselves from promiscuity and not commit adultery. Keywords: Decision, Marriage Dispensation, Malang City Religious Court. Abstrak: Artikel ini membahas tentang putusan Pengadilan Agama Kota Malang No. 0306/Pdt.P/2020/PA.Mlg tentang dispensasi kawin. Penelitian ini adalah penelitian kepustakaan dan bersifat kualitatif. Sumber data primer adalah putusan No. 0306/Pdt.P/2020/PA.Mlg tentang dispensasi kawin, ditunjang dengan sumber data sekuler dari buku dan jurnal. Data yang didapat dianalisis secara yuridis. Hasil penelitian menyimpulkan bahwa dalam putusan No. 0306/Pdt.P/2020/PA.Mlg tentang dispensasi kawin, hakim mengabulkan permohonan pemohon dengan pertimbangan calon istri telah hamil 2 bulan, dan didasarkan pada kaidah dar’ al-mafasid muqaddam ala jalb al-mashalih, maka demi kemaslahatan bersama khususnya untuk calon istri dan calon anak yang dikandung. Berdasarkan  PERMA Nomor 5 Tahun 2019 tentang Pedoman mengadili Permohonan Dispensasi Kawin dan Undang-undang Perkawinan Nomor 1 Tahun 1974 tentang Perkawinan, maka putusan hakim tersebut tidak menyalahi aturan yang berlaku. Berdasarkan hal tersebut diharapkan agar masyarakat khususnya remaja untuk menjaga diri dari pergaulan bebas dan tidak melakukan zina. Kata kunci: Putusan, Dispensasi Kawin, Pengadilan Agama Kota Malang.